Laboratory Evaluation of the Entomopathogenic Fungi Penicillium Marneffei and Verticillium lecanii Against Culex Pipeins Molestus - Rabah H Saady1 , Abdulrahman Jihad Mansoor2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background:The biological efficacy of Penicillium marneffei ,Verticilluim lecanii in the biological controlof the second and third larval phases and adult male and female mosquitoes was studied.Culex pipeinsmolestus. Aim of the study: This research aimed to isolate P. marneffei and V.lacanil associated with C.pipeines mosquitoes and compare the biological efficiency of P. marneffei and V. lecenii in their biologicalcontrol second and third instar and adult for the Cx.pipeins.Materials and methods: study was conducted fora period of 3 months from March 2020 to May 2020. Results: killing increased with increasing concentrationdue to an increase in the number of developing spores The results of the laboratory tests are shown V.lecaniifungi. at concentration 2 × 67 spore / ml highest mortality ratio 89.63% for the second larval age after 72hours, the killing rate was 81.59 % for males and 92.67% for females after 72 hours when using 2 × 67 spore/ ml . Conclusion: Entomopathogenic Fungi P. marneffei and . lecanii can use secondary metabolites in themanufacture of a fungicide for the purpose of controlling Cx.pipines mosquitoe.